Study of Plant Succession in Kanheri National Park, Bombay - Das, R. B. (Indian Forester, 1954)
The Kanheri National Park, Bombay, falls under the moist deciduous climatic climax vegetation in which Tectona grandis and Terminalia tomentosa form fifty per cent of the trees. In one area about 300 feet high Adina cordifolia replaced almost completely the original vegetation after this moist deciduous forest was cut. On further cutting, Adina cordifolia is replaced by the Bambusa arundinacea more especially on the lower slopes of the hills near the rivers. After further cutting and disturbance a mixed shrub layer appears of Holarrhena antidysenterica, Wrightia tinctoria and Calycopteris floribunda. On cutting the plants still further and pasturing, mixed stand of Holarrhena antidysenterica, Themeda triandra Setaria glauca, Celosia argentea and Pseudanthistiria heteroclita, plant succession. This is followed by Eulalia fimbriata. Finally in the area greatly trampled by man and intensively grazed by cattle Eulalia fimbriata in its turn has been found giving way to Eragrostis unioloides which forms the sixth stage of plant succession. The ultimate result of indiscriminate pasturing, trampling and soil erosion is a ground totally rocky and stony with weeds like Blumea eriantha, Eleusine indica, Cleome viscosa, Boerhaevia diffusa and many Cyperaceae. However, Blumea eriantha having two-fold advantage of propagating itself vegetatively by stolons as well as by its light cypsella fruits, wins the ground and the seventh or the final stage of degradation is reached where in Blumea eriantha is dominating. If, however, the vegetation is burnt at stages 2, 4 or 5 the ground in the next season is covered by Pogostemon parviflorus. Thus it has been observed that as a result of intensive biotic activities moist deciduous forest has been reduced to mere grassland in Kanheri National Park, Bombay.